Resource-Efficient Growth In The EU’s Sustainable Development – A Comparative Analysis Based On Selected Indicators - Lipińska, Danuta (Comparative Economic Research. Central and Eastern Europe, 2016)
This article presents a theoretical and empirical analysis of resource efficiency in the use of natural resources for economic growth consistent with the principles of sustainable development in EU countries. To realize this objective, a review of the literature and EU strategic documents concerning the subject under study is presented. The comparative analysis has been prepared on the basis of international statistical data (Eurostat, EEA) for EU countries from the years 2002–2013. The analysis covers the following indicators: resource productivity, water exploitation index, water productivity, generation of waste, and the landfill and recycling rate. The results show that in general terms the efficiency of resource use in the EU is gradually improving, but only to a small extent. With regard to individual countries this process shows significant diversity, and is closely associated with the level of economic development of a particular country. In some individual countries, this resource efficiency is at a very low level, which is the case with several countries of Eastern and Central Europe.